AMStrength program in Canadian federal correctional services: correctional officers’ views and interpretations - Ricciardelli, Rose (Promoting wellness and resiliency in correctional officers, 2023)
Scholars and correctional officials have begun to recognize the association of correctional work with occupational stressors that deteriorate mental health and well-being. Yet, programs and policies to support prison staff as they navigate physical, emotional, and psychological challenges are limited, with scarce empirical evidence supporting their usefulness to employees. We examine the Advanced Mental Strength and Conditioning (AMStrength) program using semi-structured interviews with 70 correctional officers after they completed a year on the job. Among our findings, we highlight that 80% of participants have not used AMStrength since being their training during recruitment. However, AMStrength fulfills a vital role in promoting awareness, including self-awareness of mental health.